(untitled) (Research, Society and Development, 2022)
Studies reporting the link between animal abuse and interpersonal violence are scarce in Brazil, where domestic violence reached epidemic proportions in recent decades. This cross-sectional study included data from 351 women received in a Specialized Police Station in the city of Belo Horizonte, Brazil, from November 2019 to February 2020, victims of domestic violence. For risk factors analysis, two logistic models were adjusted: one responding to the presence of animal abuse and the other to the presence of violence against the victim’s child.The victim being the pet’s guardian (OR 2.85, 95%CI 1.17 - 7.69), the victim having suffered psychological harassment (OR 2.56, 95%CI 1.02 - 7.02) and alcohol consumption in the home environment (OR 3.26 95%CI 1.47 - 7.52), were risk factors for animal abuse. The existence of a conflicting relationship between the victim’s children and the perpetrator (OR 4.08, 95%CI 1.79 -9.71), the consumption of drugs and alcohol in the domestic environment (OR 2.85, 95%CI 1.27 - 6.67), the victim being the guardian of pets (OR 2.42, 95%CI 1.07 - 5.70 ) and the victim being the perpetrator’s ex- wife (OR 3.92, 95%CI 1.70 - 9.51)were risk factors for violence against the victims’ children . The study provides evidence that the various types of domestic violence that women suffer are significantly associated with violence against pets and children and adolescents, especially psychological and physical violence. Given this, this study indicates that strategies for prevention and controlling for domestic violence should occur in a multidisciplinary way, providing an One-Health approach.